Control system for neuro-prostheses integrating induced and volitional effort∗. Issue 20 (2015) - Ambrosini, E.; Schauer, T.; Klauer, C.; Pedrocchi, A.; Ferrigno, G.; Ferrante, S.
Abstract: To increase the rehabilitation outcomes of stroke patients with weak residual muscle activity, a novel control strategy for Functional Electrical Stimulation (FES) was designed and tested during a tracking task. The system includes an electromyography (EMG)-based feedback controller and a trial-to-trial adaptation of the FES support. The first modulates the stimulation intensity to achieve a desired amount of FES-evoked muscle activity corresponding to a desired FES-induced angular support trajectory. The second iteratively updates this trajectory in order to minimize the error between the target displayed to the patient and the measured angle trajectory. This support adaptation only takes place in case the subject actively contributes to the movement. If the estimated volitional effort is too low, FES support is quickly withdrawn to remind the subject to actively contribute to the tracking task. The EMG signal of the stimulated muscle is used to estimate both the FES-induced and the volitional muscle activity. The feasibility of the proposed control scheme was experimentally investigated in one healthy subject by stimulating the medial deltoid muscle to support shoulder abduction. First, the controller was tested simulating different volitional contributions of a potential patient. The control system adjusted the amount of FES-support as expected. Then, the compensation of muscle fatigue by the feedback controller was demonstrated by repeatedly applying the same desired FES-induced angular trajectories, while the subject was asked to be relaxed. As a result, the control system was able to provide the desired support for about 7 minutes until the stimulation intensity saturated.